Effects of roads and log hauling on woodland caribou use of a traditional wintering area near Armstrong, Ontario - Hyer, Bruce T. (1997)
Increasing concern for the viability of forest-dwelling woodland caribou (Rangifer tarandus caribou) in Ontario has resulted in recommendations for more restrictive timber harvesting practices. Caribou populations have steadily retreated northward except for small remnant populations. While there is much agreement that the fundamental cause of the decline is timber management. there is much less agreement on the proximate causes. Debate has focussed upon three causal hypotheses: 1) habitat degradation or change: 2) predation: and 3) displacement or stress by human activities in critical habitats such as wintering or calving areas. A three-year field experiment (fall 1990-spring 1993) tested the third hypothesis and showed that woodland caribou significantly altered their winter dispersion when log trucks drove through their traditional wintering area. All radio-collared caribou that occupied the experimental area moved 8-60 km after log hauling began. Track counts indicated that most caribou moved 3-60 km away from the road after it was plowed and hauling commenced. often into range that had fewer lichens and more predators than winter refugia. In a nearby undisturbed control area. no such movements occurred. The Wabinosh Road prime study area bisects a traditional wintering area of open-stocked mature jack pine (Pinus banksiana Lamb.) and black spruce (Picea mariana (Mill.) B.S.P.) with lichen ( Cladina spp.) ground cover. Caribou presence and movements were monitored by fixed-wing aircraft using both high-level telemetry and low-level transects recording tracks. Pronounced habitat partitioning between moose (Alces alces) and caribou excluded moose from the caribou wintering area. Grey wolf (Canis lupus) tracks were frequently associated with the moose tracks., but rarely near caribou tracks. No wolf predation on caribou was observed within the winter refugia: three kills were found outside them. Wolf predation was almost exclusively upon moose. frequently utilizing roads and human trails to access them. Due to the possibility of displacing caribou from winter refugia to places with higher predation risk. winter log hauling through caribou winter habitat should be avoided wherever possible.